La Familia Cristiana en el contexto de la Familiaris Consortio de San Juan Pablo II (2022)
This research aims to build a pastoral theological reflection on the family in light of the Familiaris Consortio of John Paul II. At the methodological level, the article is constructed in two moments. In the first, an assessment is made of the theological-pastoral contribution on the family, given by John Paul II. In a second moment, the contributions given in the encyclical are assumed, in order to illuminate the ecclesial reality of the parish communities of the municipalities of Cocorná and San Rafael. The authors of are convinced that the various realities such as suicide and domestic violence experienced between communities, can be faced from the teaching given by John Paul II.